Environmental chemistry an analytical approach - Overway, Kenneth S. 1971- (John Wiley and Sons, 2017)
"With a focus on quantitative measurements, Environmental Chemistry provides the reader with the essential chemical principles that drive environmental processes. The author puts the state of the current environment in the context of the formation and evolution of the planet while reviewing chemical fundamentals. To prepare students for quantitative measurements, an entire chapter is devoted to measurement statistics and quantitative methods of analysis. A concise yet detailed explanation of the chemistry that underlies the atmosphere, lithosphere and hydrosphere gives students the requisite knowledge to understand issues such as ozone formation, the greenhouse effect, soil chemistry and water quality. Each chapter concludes with descriptions of the methods used in the analysis of environmentally significant chemicals. In-chapter and end-of-chapter problems train the students in analysis techniques and develop a chemically rigorous understanding of the environment. An appendix provides a detailed description of major chemical instruments students are likely to use in an undergraduate laboratory"--